KANDUNGAN NILAI AJARAN â€œMEMANGUN RESEP TIYASING SASAMAâ€ PADA RAGAM HIAS GERBANG KOMPLEKS MAKAM SUNAN DRAJAT - Sadah, Khozinatus; D, Achmad Haldani; Sachari, Agus (JURNAL ISLAM NUSANTARA, 2018)
Sunan Drajat is one of the spreaders of Islam in the northern coast of Java island in the XV - XVI century by utilizing local culture as a medium of daâ€™wah, one of which is in the form of religious symbols contained in decoration. At present, the tomb complex of Sunan Drajat is a religious tourist destination in Lamongan that can increase regional income, with visitors reaching 440 thousand people, in 2016. This study used a qualitative approach with aesthetic analysis, the morphology of Thomas Munro, aesthetic studies of Islam by Al Faruqi, and its meaning was carried out synchronously based on local oral traditions. The results showed that the decoration contained the meaning of Sunan Drajat's teachings and thoughts, namely memangun resep tyasing sasomo (we always make others happy), while the morphology consisted of lines, dots, expressions that formed a pavilion, mountains and tree of life. Aesthetic is achieved by a symmetrical arrangement with a pinch and focus in the center. Thus, the decoration at the main gate of the tomb complex of Sunan Drajat includes the media preaching the teachings of Sunan Drajat